PROFIL KECEMASAN IBU HAMIL DALAM MENGHADAPI PROSES PERSALINAN DI KANAGARIAN LAKITAN KECAMATAN LENGAYANG KABUPATEN PESISIR SELATAN - Melka, Musda Rukmana; Kasih, Fitria; Nofrita, Nofrita (Bimbingan dan Konseling, 2013)
This research described about an anxious of the pregnant women toward the process of giving birth. Based on preliminary study through interview, it was found that the women who were pregnant felt anxious in the process of giving birth. This research focused on (1) The profile of pregnant women toward the process of giving birth physiology (2) The profile of pregnant women toward the process of giving birth psychology. This research was descriptive qualitative. The technique of collection sample is by using snow ball sampling. The core instrument of this research is pregnant women. The additional instrument are the doctor, and the husband of pregnant women who ever given birth. The collection of the data is through interview, observation, and documentation. This data was tested by triangulation and member check. After that this data was analyzed through three steps: 1.Data reduction. 2.Confirmation. 3.ConclusionThe result of this research; it was found that the profile of pregnant women toward the process of giving birth physiology was: heart beating, the pain before giving birth, unsleeping, and sweat. The profile of pregnant women toward the process of giving birth psychology was: worry, panic, anxious, and nervous